Activities of Selling and Buying Non-Halal Certified Meat in Review of Islamic Business Ethics and Fiqh Muamalah - Afifah, Wahyu Nabil; Syihabudin; Muhammad Abduh (Universitas Muhammadiyah Surabaya, 2024)
This study aims to determine the activities of buying and selling non-halal certified meat in terms of Islamic business ethics according to Syed Nawab Haider Naqvi and Fiqh Muamalah. Because in buying and selling activities in the Kukun Traditional Market, Rajeg District does not pay attention to halal certification on the goods it sells or buys. Many meat traders do not have halal certification and meat buyers who do not make sure whether the meat they buy is cut according to Islamic law. So this research discusses business ethics according to Syed Nawab Haider Naqvi which has 4 principles, namely: Tawhid (unity), Balance, Freewill, and Responsibility. When viewed from Islamic business ethics, meat traders have implemented Islamic business ethics such as Tauhid (unity), Balance, Freewill, and Responsibility in their business activities. However, when viewed from fiqh muamalah which is seen from the side of non-halal certified meat traders in the Kukun Traditional Market, Rajeg District, it is still allowed. It's just that the slaughter process is in accordance with Islamic law and the meat is not contaminated with haram substances. However, meat traders in the Kukun Traditional Market should obtain halal certification, because in line with Sadd Adz-Dzari'ah halal certification can protect consumers from consuming haram meat or bringing Mufsadah. And when viewed from the side of consumers who do not ensure that the meat is slaughtered according to Islamic law, the meat they buy may be consumed, it's just that it's better for consumers to buy meat that has pocketed halal certification so that the slaughter process is in accordance with Islamic law. If consumers doubt that meat traders do not say Basmallah, consumers only need to be prejudiced and then when they want to eat it, they must recite Basmallah.